Impact of habitat loss on animal diversity (Zoological Records and Reviews, 2024)
Habitat loss is the single most important driver of global animal biodiversity decline, yet the dose-response relationshipbetween habitat area reduction and species richness loss varies substantially across taxa, landscape contexts, andspatial scales. This study quantifies the impact of habitat loss on animal diversity across four taxonomic groups -- groundbeetles (Carabidae), breeding birds, amphibians, and small mammals -- in agricultural landscapes spanning a 10-92%natural habitat loss gradient in Germany, Sweden, and Denmark (n = 72 study sites, 2020-2023; n = 18,641 individualrecords across 312 taxa). Species-area relationships (SARs) were modelled for each taxon using the power function (S =cA^z); z-values ranged from 0.18 (small mammals) to 0.41 (amphibians), with amphibians and birds showing thesteepest diversity-area declines. Threshold analysis identified non-linear diversity collapses at 68-74% habitat loss forbirds and amphibians, consistent with habitat amount thresholds documented in global meta-analyses. Functionaldiversity (functional richness, evenness, and divergence) declined more steeply than taxonomic diversity across thehabitat loss gradient for all four groups (mean Hedges' g = -0.84 vs. -0.61 for taxonomic), indicating disproportionate lossof functionally unique species. Landscape connectivity (measured as the proportion of natural habitat within 2 km radius)significantly moderated the habitat loss-diversity relationship for mobile taxa (birds: interaction term beta = 0.31, p =0.004), but not for amphibians (p = 0.18), underscoring the dispersal barrier created by intensively managed agricultural matrices for low-mobility species. These findings quantify evidence-based habitat retention thresholds applicable to landscape planning under the EU Nature Restoration Law targets.
Keywords: EU Nature Restoration Law; biodiversity decline; agricultural landscape; amphibians; Carabidae; landscape connectivity; habitat threshold; functional diversity; species-area relationship; habitat loss